2005
DOI: 10.1007/s10529-005-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of β-glucans of Agaricus brasiliensis in Different Stages of Fruiting Body Maturity and their Use in Nutraceutical Products

Abstract: beta-Glucans of Agaricus brasiliensis fruiting bodies in different stages of maturity were isolated and characterized by FTIR and NMR. These fractions had greater amount of (1-->6)-beta-glucan and the (1-->3)-beta-glucan increased with fruiting bodies maturation. Yields of beta-glucans increased from 42 mg beta-glucans g(-1) fruiting bodies (dry wt) in immature stage to 43 mg g(-1) in mature stage with immature spores, and decreased to 40 mg g(-1) in mature stage with spore maturation. Mature fruiting bodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 12 publications
5
40
1
2
Order By: Relevance
“…However, da Eira [9] reported that A. subrufescens OB has higher b-glucan concentration, and consequently better cellular protection compared to CB. Camelini et al [7] suggested the use of OB instead of CB as functional food because there is a higher quantity and diversity of b-glucans in it. The best results found in our work for OB agree with the ones found in da Eira [9] and Camelini et al [7], suggesting that bglucan, found in greater amounts and variety in OB, may be the responsible for the antimutagenic activity on A. nidulans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, da Eira [9] reported that A. subrufescens OB has higher b-glucan concentration, and consequently better cellular protection compared to CB. Camelini et al [7] suggested the use of OB instead of CB as functional food because there is a higher quantity and diversity of b-glucans in it. The best results found in our work for OB agree with the ones found in da Eira [9] and Camelini et al [7], suggesting that bglucan, found in greater amounts and variety in OB, may be the responsible for the antimutagenic activity on A. nidulans.…”
Section: Discussionmentioning
confidence: 99%
“…According to da Eira [9] and Cameline et al [7], an opened basidiocarp of A. subrufescens presents higher concentration and diversity of ß-glucans and probably higher biological activity than a closed basidiocarp. On the other hand, a closed basidiocarp of A. subrufescens has higher antioxidant and anti-inflammatory activities than an opened basidiocarp [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The technical protocol used to obtain the polysaccharide-rich fractions from Agaricus blazei was adapted from Camelini et al (2005) and Meng et al (2008). Briefly, 20 g of fresh and dried fruiting body of Agaricus blazei (Energy Vita ® , lot #1, harvest in 2013) was macerated in 400 mL of ethanol 85% (v/v), with the solution heated for 3 h at 80°C.…”
Section: Purification Of Polysaccharide-rich Fractions From Agaricus mentioning
confidence: 99%
“…Extraction and purification were performed as stated in Camelini et al (2005), also chemical analysis is presented in the mentioned work.…”
Section: Extraction and Purification Of The Polysaccharide Fractionmentioning
confidence: 99%